Rhapis excelsa: Lady Palm - Timothy K. Broschat (EDIS)
Rhapsis excelsa, the lady palm, is an outstanding, small clustering palm for shady landscape or interiorscape use. This 2-page fact sheet gives a brief overview of the Lady Palm. Written by Timothy K. Broschat and published by the Environmental Horticulture Department, August 2016.